Clinical value of soluble urokinase-type plasminogen activator receptor in predicting sepsis-associated acute kidney injury - Wenwen Zhang; Yue Gu; Jing Zhou; Juntao Wang; Xiaoru Zhao; Xiaoyu Deng; Han Li; Lei Yan; Xiaojing Jiao; Fengmin Shao (Renal Failure)
Background Sepsis-associated acute kidney injury (S-AKI) is a critical illness and is often associated with high morbidity and mortality rates. The soluble urokinase-type plasminogen activator receptor (suPAR) is an important immune mediator and is involved in kidney injury. However, its diagnostic value in S-AKI patients remains unclear. Therefore, we assessed the early predictive value of suPAR for S-AKI patients.Methods We prospectively enrolled adult patients, immediately after fulfilling the sepsis-3 criteria. Plasma suPAR levels at 0-, 12-, 24-, and 48-h post-sepsis diagnosis were measured. S-AKI development was the primary outcome. S-AKI risk factors were analyzed using logistic regression, and the value of plasma suPAR for early S-AKI diagnosis was assessed using receiver operating characteristic (ROC) curves.Results Of 179 sepsis patients, 63 (35.2%) developed AKI during hospitalization. At 12-, 24-, and 48-h post-sepsis diagnosis, plasma suPAR levels were significantly higher in patients with S-AKI than in patients without S-AKI (p < 0.05). The plasma suPAR had the highest area under the ROC curve of 0.700 (95% confidence interval (CI), 0.621–0.779) at 24-h post-sepsis diagnosis, at which the best discrimination ability for S-AKI was achieved with suPAR of ≥6.31 ng/mL (sensitivity 61.9% and specificity 71.6%). Logistic regression analysis showed that suPAR at 24-h post-sepsis diagnosis remained an independent S-AKI risk factor after adjusting for mechanical ventilation, blood urea nitrogen, and pH.Conclusions The findings suggest that plasma suPAR may be a potential biomarker for early S-AKI diagnosis.